PENGARUH PERLAKUAN VARIASI JENIS GULA TERHADAP TINGKAT KESUKAAN DODOL PEPAYA (Carica vasconcellea) - Sukmawati -; Methatias Ayu M; Lina Widawati (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Papaya ( Carica vasconcelea ) is a tropical fruit that has a high nutrient content. In general, ripe papaya fruit is consumed directly, but can also be processed into food products such as papaya “dodol”. “Dodol” is one of the processed fruit products are included in this type of semi- moist food consisting of a mixture of rice flour and sugar . To produce papaya “dodol” accordance with the expected quality used some kind of sugar in the making. This study aims to determine the level of papaya “dodol” a panelist to both of the parameters of color , flavor and texture. The treatments used in this study is a combination of sugars , namely the addition of brown sugar and granulated sugar , brown sugar and coconut sugar , coconut and sugar and granulated sugar. The analysis used in this study is the organoleptic analysis. From the results of this research is that in terms of the parameters of color , papaya “dodol” most preferred is the treatment of papaya with the addition of palm sugar and coconut sugar . In terms of taste parameters , papaya”dodol” most preferred is the treatment of papaya with the addition of brown sugar and granulated sugar . In terms of texture parameters , papaya “dodol” most preferred is the treatment of papaya with the addition of brown sugar and granulated sugar.Keywords : Papaya “dodol” , sugar , Preferrency